Understanding Types of Stigma Experienced in Black Women Living With HIV in Baltimore, Maryland: A Mixed Methods Study - Tanya Mikhael; Kyra Jennifer Waligora Mendez; Chun‐An Sun; Joy Chepkorir; Hae‐Ra Han (Nursing Open)
ABSTRACT Aim To understand how Black or African American women living with HIV (WLH) experience different types of stigma in their daily lives. Design Secondary analysis of quantitative and qualitative data from a recent clinical trial in Baltimore, Maryland. Methods Quantitative data were collected in the baseline survey, and qualitative data were gathered during 6‐month follow‐up focus group and individual interviews. First, we conducted an exploratory factor analysis with principal axis factoring to identify the underlying factor structure of the HIV Stigma Scale. Next, we analysed the interviews with thematic analysis to understand women's experience with different stigma types. Results Exploratory factor analysis revealed the HIV Stigma Scale was a one‐factor scale that measured internalised stigma. However, qualitative interviews revealed that four different types of stigma were present in the everyday lives of WLH. These included the following: vicarious, enacted, internalised and perceived stigma. A current HIV stigma scale may not fully capture the stigma experiences salient to Black WLH. There is a need for internally valid quantitative measures that can adequately capture HIV stigma as experienced by Black WLH. Patient or Public Contribution Black WLH agreed to participate in the study, completed the HIV stigma scale and shared their experiences with us.